A case of uncorrected tetralogy of Fallot with preeclampsia: an anesthetic challenge for cesarean section - Bhar, Debasish; Maji, Sunanda; Das, Aditi; Bhar (Kundu), Sudeshna; Mandal, Ratan Chandra (Journal of Society of Anesthesiologists of Nepal, 2016)
Women with cardiovascular diseases may present for cesarean delivery. We present a case of anesthetic management for cesarean section in a patient with uncorrected tetralogy of Fallot complicated with preeclampsia. No definite guideline or information is available in the textbook or literature about the management of such a case. A 21 year primigravida was admitted in our institute with breathlessness on normal day to day life activity. Her blood pressure was 160/100 mmHg, oxygen saturation 85-86% in room air and she had ejection systolic murmur of grade three intensity along the left sternal border. Her echocardiography which was done in the first trimester revealed tetralogy of Fallot with moderate to severe right ventricular outlet obstruction with hypoplastic pulmonary artery and pulmonary valve. Proteinurea was detected on bedside urine examination. The patient was posted for emergency cesarean section due to non-reassuring fetal heart rate associated with preeclamsia. Magnesium sulfate 10 gm intramuscularly was given for seizure prophylaxis and general anesthesia was administered using etomidate as induction agent. The objective of anesthetic management mainly depends on maintaining of systemic vascular resistance and decreasing pulmonary vascular resistance. In preeclampsia systemic vascular resistance is already elevated. Thus treatment of preeclampsia may worsen cyanosis, so we avoided labetalol to reduce blood pressure. Intra-operative and post-operative periods were uneventful and baby had good apgar scores. So we can conclude that cesarean section in patient with both tetralogy of Fallot and preeclampsia can be managed successfully with general anesthesia using techniques which maintain systemic vascular resistance.